Corporate Financialization in Brazil: The "Big Three" Blockholders and Horizontal Ownership - Vicente Gonçalves da Cruz, Wilton; Sacomano Neto, Mário (Review of Business Management, 2024)
Purpose – Institutional investing has grown at an unprecedented rate in recent decades. Three major firms dominate the industry worldwide: BlackRock, Vanguard Group and State Street, or the "Big Three." This study investigates the strategy of blockholders in the ownership of companies operating in the Brazilian economy from the perspective of strategic action field theory. Theoretical framework – The growth of international institutional investors as shareholders in the corporate market is associated with the strengthening of the financialization process. Strategic action field theory allows the study of conflict and cooperation relationships between actors in economic and business contexts, as well as changes in these fields. Design/methodology/approach – This study proposes an exploratory and descriptive analysis using a sample of 200 large companies operating in Brazil. Also, Pearson’s correlation measures and multiple correspondence analysis (MCA) were calculated to understand the relationships between shareholding variables and investments in sectors of activity. Findings – These institutional investors are present in most of the equity positions and the results suggest horizontal ownership investments in the portfolio of the "Big Three" in the large companies operating in Brazil. Their investment portfolios are focused on industries and segments with high economic value through horizontal ownership. Practical & social implications of research – The actions of these three major investors affect aspects of corporate governance and influence the economy as a whole. Originality/value – This article presents an original analysis of the investments of the "Big Three" as shareholders in companies operating in Brazil. This paper also addresses the intensification of the phenomenon of financialization and its links with the emergence of institutional investors as shareholders in large companies.